2018
DOI: 10.1123/jsm.2017-0031
|View full text |Cite
|
Sign up to set email alerts
|

Student-Athletes’ Organization of Activism at the University of Missouri: Resource Mobilization on Twitter

Abstract: Although social media has been increasingly noted as an outlet for athletes to openly address social issues, there has been very little systematic examination on the organizational capacity of social media. To address this, our study seeks to focus on the strike organized by the football players through Twitter at the University of Missouri in 2015. Specifically, it adopts the theoretical framework of resource mobilization and conducts a comprehensive analysis composed of two parts. First, by identifying geogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 33 publications
3
68
0
Order By: Relevance
“…In recent years, social media has become a forum for activism, and student‐athletes participate in this behavior as well (Yan, Pegoraro, & Watanabe, ). For example, in 2015, football players at the University of Missouri, indicated they would not play again until university leadership was changed (Frederick, Sanderson, & Schlereth, ).…”
mentioning
confidence: 99%
“…In recent years, social media has become a forum for activism, and student‐athletes participate in this behavior as well (Yan, Pegoraro, & Watanabe, ). For example, in 2015, football players at the University of Missouri, indicated they would not play again until university leadership was changed (Frederick, Sanderson, & Schlereth, ).…”
mentioning
confidence: 99%
“…Jackson and Welles [ 47 ] analyzed the network of retweets and mentions with the #Ferguson hashtag on Twitter and found that the network was a broadcast network, where a small number of influential users transmit messages to the vast majority of users unilaterally. Yan et al [ 48 ] also analyzed the network of retweets and mentions on Twitter to reach similar results, revealing that the #ConcernedStudent1950 hashtag network has evolved to be highly concentrated. Wang et al [ 49 ] paid attention to the hashtag co-occurrence network; their analysis of tweets with #OccupyWallStreet revealed that the role of hashtags in information virality may vary with the context of the tweets.…”
Section: Related Workmentioning
confidence: 86%
“…However, Twitter has a high appeal among sport fans (Burns, 2014), as through a live feed of comments, Twitter serves as a simultaneous shared experience with people all over the world (Harrington, Highfield, & Bruns, 2012). It has also been explored in depth by sport scholars interested in the nexus between the passion of sport and the instantaneity of the microblogging site (Li et al, 2019;O'Hallarn et al, 2019;Yan, Pegoraro, & Watanabe, 2018).…”
Section: Review Of Literaturementioning
confidence: 99%